2022
DOI: 10.1155/2022/1900403
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Bone Marrow-Derived Mesenchymal Stem Cells against a Monoiodoacetate-Induced Osteoarthritis Model in Wistar Rats

Abstract: Osteoarthritis (OA) of the knee is a debilitating condition that can severely limit an individual’s mobility and quality of life. This study was designed to evaluate the efficacy of bone marrow-derived mesenchymal stem cell (BM-MSC) treatment in cartilage repair using a rat model of monoiodoacetate- (MIA-) induced knee OA. OA was induced in the knee joint of rats by an intracapsular injection of MIA (2 mg/50 μL) on day zero. The rats were divided into three groups ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…The osteoarthritic group had a substantial drop in serum GSH content in the current investigation. This is consistent with other previous publications [70,71].…”
Section: Discussionsupporting
confidence: 94%
“…The osteoarthritic group had a substantial drop in serum GSH content in the current investigation. This is consistent with other previous publications [70,71].…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, MSCs are also able to avoid T-cell proliferation and ensure macrophage polarization [ 244 , 245 , 246 ]. Similarly to our study, other researchers described the up-regulation of IL-10 and down-regulation of IL-1β, IL-6, and TNF-α in OA joint by MSCs exposition [ 247 , 248 ]. Nevertheless, the efficacy of cell-based treatment is affected by many factors including joint state and etiology of the degenerative process.…”
Section: Discussionsupporting
confidence: 87%
“…C57BL, DBA1, and FVBN mice express the SCA-1 surface marker [ 39 ], while BALB/C mice express SCA-1 [ 40 ]. MSCs are readily accessible and can be isolated from the stroma of almost all organs, with a relatively straight forward isolation process [ 41 ]. MSCs have demonstrated notable efficacy in the treatment of autoimmune diseases and tissue/organ repair.…”
Section: Mechanisms Of Oamentioning
confidence: 99%
“…Hamdalla HM et al found that BM-MSCs significantly alleviated inflammation in a monosodium iodoacetate (MIA)-induced KOA rat model, improving knee joint swelling. A single intra-articular injection of BM-MSCs markedly downregulated IL-1β, IL-6, and TNF-α while upregulating IL-10 and TGF-β [ 41 ]. Chahal J et al observed a reduction in the levels of the proinflammatory factors IL-12 and p40, decreased proinflammatory monocyte and macrophage subpopulations, and decreased synovial inflammation in late-stage KOA patients after BM-MSC injection, leading to improved passive joint mobility [ 60 ].…”
Section: Application Of Mscs From Different Sources In Oa Therapymentioning
confidence: 99%